Komunikasi Non Verbal Penutur Bahasa Jepang dalam Acara Variety Show Jepang - Mamoto, Christine Jeanny; Handayani, Umi (Journal of Japanese Language Education and Linguistics, 2018)
All people use non verbal communication in their daily activities. But sometime, they dont realize that they are doing it. This research investigated about non verbal commu- nication that is used by the Japanese speaker. The part of this non verbal communication that was investigated in this research was emblem. Emblem is a sign that is used to substitude a word that has a meaning. Emblem is a gesture which is used consciously and consists cultures from each region. This research used a descriptive methode. It was trying to illustrate this three research problems. They were: what kind of non verbal com- munication that the Japanese speakers use, what are the meanings of the gestures, and in what kind of situation that the Japanese speaker will use the gestures. The purposes of this research was to illustrate the non verbal communication that the Japanese speaker use, the meanings of the non verbal communication gestures, and also the situations when they use the gestures. From the research, 29 emblems were found. Each of them has its meanings and functions, and is being used according to its meanings and func- tions.Â